Attitudes of Senior Management in Algerian Economic Companies towards the Digitization of Human Resource Management (Al-Mansour Journal, 2023)
This research aims to highlight the role and impact of the applications of electronic management of human resources E-HRM in improving the performance of the Algerian public economic companies. The field study included a sample of Algerian public economic companies, where we distributed 33 questionnaires in order to know the degree of integration of digitization in human resource management and the extent of its impact on organizational performance, through achieving efficiency and creating added value, and improving its competitiveness in the markets. We also used (SPSS/V21), (PLS/v3) and (Excel 2010) in the general consistency test of the study tool, the statistical analysis of its axes, and the research hypothesis test. According to the results of our study, we can say that the integration of digitization into human resource management practices at the level of public companies is limited only to the electronic management of documents and wages, and is not commensurate with the developments in terms of technology, the requirements of modernity and the intensity of competition in the markets.
Keywords: Organizational Performance; Electronic management of human resources; Digitization